PENGARUH KONSENTRASI GULA DAN CABAI TERHADAP UMUR SIMPAN MANISAN CEREMAI BASAH (Phyllanthus acidus) - Te'ne, Fitria; Lahming, Lahming; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aimed to determine the effect of sugar and chili concentrations on the characteristics of candied wet ceramai (texture, flavor, aroma, and color) and to know the content of water content, rendement, sugar of reduction , total acid, vitamin C and visual test. The design used in the study is completely randomized factorial design (RAL Factorial). Data analysis technique used is the analysis of variance using SPSS version 21..The results showed that the concentration of sugar and chili influenced water content, reducing sugar, vitamin C, total acid, and organoleptic test. The longer the storage, the water content increases while the sugar content, vitamin C, total acid and organoleptic test decreases. Sugar concentration 40% chili 1% gives the best quality of candied wet ceremai during storage